Comprehensive Midwifery Care For Ny’’H’’ With Normal Pregnancy At Bontobangun Health Center,Rilau Ale District,Bulukumba Regency - Asririn, Asririn; Juniarli, Sri Eka; Irmawati, Irmawati (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Midwives play an important role in efforts to improve maternal and child health, one of which is by implementing comprehensive midwifery care. Midwifery care is carried out to detect early things that may occur during pregnancy, childbirth, newborns, postpartum, neonates and family planning services. The aim is to provide comprehensive care to Mrs